The safety and efficacy of a new anticoagulation strategy using selective in-circuit blood cooling during haemofiltration--an experimental study - Krouzecky, Ales; Chvojka, Jiri; Sykora, Roman; Radej, Jaroslav; Karvunidis, Thomas; Novak, Ivan; Hanzlikova, Jana; Bultasová-Přibylová, Lenka; Ruzicka, Jiri; Petrankova, Zuzana; Matejovic, Martin (Nephrology, dialysis, transplantation, 2011)
BACKGROUND: Selective in-circuit blood cooling was recently shown to be an effective anticoagulation strategy during short-term haemofiltration. The aim of this study was to examine the safety of this novel method and circuit life. METHODS: Fourteen pigs were randomly assigned to receive continuous haemofiltration with anticoagulation achieved either by selective cooling of an extracorporeal circuit (ECC) (COOL; n = 8) or through systemic heparinization (HEPARIN; n = 6). Before (T0) as well as 1 (TP1) and 6 h (TP6) after starting the procedure the following parameters were assessed: animal status, variables reflecting haemostasis, oxidative stress, inflammation and function of blood elements. RESULTS: All animals remained haemodynamically stable with unchanged body core temperature and routine biochemistry. Regional ECC blood cooling did not alter clinically relevant markers of haemostasis, namely activated partial thromboplastin and prothrombin times, thrombin-antithrombin complexes, von Willebrand factor and plasminogen activator inhibitor-1. Platelet aggregability, serum levels of free haemoglobin, leukocyte count, oxidative burst and blastic transformation of T-lymphocytes were all found to be stable over the treatment period in both groups. ECC blood cooling affected neither plasma malondialdehyde concentrations (a surrogate marker of oxidative stress) nor plasma levels of cytokines (tumour necrosis factor-α, interleukin-6 and -10). While the patency of all circuits treated with systemic heparin was well maintained within the pre-selected period of 24 h, the median filter lifespan in the COOL group was 17 h. CONCLUSION: Utilizing clinically relevant markers, selective in-circuit blood cooling was demonstrated to be a safe and feasible means of achieving regional anticoagulation in healthy pigs. The long-term safety issues warrant further evaluation.
Keywords: zvířata; oxidační stres; modely nemocí na zvířatech; Swine; prasata; zánět; Animals; Inflammation; hemokoagulace; hemofiltrace; Renal Insufficiency; mimotělní oběh; heparin; Blood Coagulation; Disease Models, Animal; interleukin-6; renální insuficience; antikoagulancia; Extracorporeal Circulation; Heparin; Anticoagulants; Oxidative Stress; Hemofiltration; Interleukin-6